Psychiatric adverse events associated with GLP-1 receptor agonists: a real-world pharmacovigilance study based on the FDA Adverse Event Reporting System database - Chen, Wei; Cai, Peishan; Zou, Wenbin; Fu, Zhiwen (Frontiers in Endocrinology, 2024)
Background Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are widely used due to their profound efficacy in glycemic control and weight management. Within real-world contexts, the manifestation of certain psychiatric adverse events (AEs) has been observed, which is potentially linked to the administration of GLP-1 RAs. The objective of this study was to undertake a comprehensive investigation and characterization of the psychiatric AEs associated with GLP-1 RAs. Methods We retrieved reports of AEs associated with treatment with GLP-1 RAs during the period from the first quarter (Q1) of 2004 to Q1 2023 from the FDA Adverse Event Reporting System (FAERS) database. Descriptive analysis was performed to examine the clinical characteristics and time to onset of the psychiatric AEs caused by GLP-1 RAs. Moreover, disproportionality analyses were performed using the reporting odds ratio (ROR) to identify GLP-1 RA-related psychiatric AEs. Results A total of 8,240 reports of psychiatric AEs were analyzed out of 181,238 AE reports with treatment with GLP-1 RAs. Among these cases, a higher percentage was represented by women compared to men (65.89% vs. 30.96%). The median age of these patients was 56 years, with an interquartile range (IQR) of 48–67 years, based on data available in 286 case reports. This study showed that the median time to onset of the overall GLP-1 RA-related AEs was 31 days (IQR = 7–145.4 days), which varied among GLP-1 RA regimens. Specifically, exenatide had a significantly longer onset time at 45 days (IQR = 11–213 days), with statistically significant differences from the onset times of the other five GLP-1 RAs (p< 0.0001). Moreover, eight categories of psychiatric AEs, namely, nervousness (ROR = 1.97, 95% CI = 1.85–2.11), stress (ROR = 1.28, 95% CI = 1.19–1.38), eating disorder (ROR = 1.57, 95% CI = 1.40–1.77), fear of injection (ROR = 1.96, 95% CI = 1.60–2.40), sleep disorder due to general medical condition—insomnia type (ROR = 2.01, 95% CI = 1.60–2.52), binge eating (ROR = 2.70, 95% CI = 1.75–4.16), fear of eating (ROR 3.35, 95% CI = 1.65–6.78), and self-induced vomiting (ROR = 3.77, 95% CI = 1.77–8.03), were defined as GLP-1 RA-related psychiatric AEs through disproportionality analysis. Conclusion Our findings demonstrate a significant association between GLP-1 RAs and the development of specific psychiatric AEs. Despite the observational nature of this pharmacovigilance study and the inherent limitations of the FAERS database, our preliminary findings in this work could provide a better basis for understanding the potential psychiatric AEs that may occur with GLP-1 RA treatment, assisting clinicians to focus on these AEs and provide early intervention for optimal risk management.